Vocabulary That Is Rarely Used by People in Kuok Village, Kuok District, Kampar Regency - Elgi; Muhammad Levi; Rafika Makhiro; Riri Zelpia; Dwi riva aini fitri; restu putri nanda (FKIP - Universitas Pahlawan Tuanku Tambusai, 2024)
This article is entitled